Adaptive Noise Cancellation Systems using Selectable Algorithm - Roshahliza, M. Ramli; Salina, Abdul Samad (Lambert Academic Publishing, 2016)
Selectable algorithms for adaptive noise cancellation systems are promoted in this book. The book deals with digital signal processing for signal enhancement, it offers a source of information related to the algorithm development and implementation of adaptive noise cancellation systems. These systems can be very useful in various real-time applications such as telecommunication, headphones, hearing aid, voice controlled system, teleconferencing and many others. The book targets DSP designers, researchers and postgraduate students in the field of DSP for mobile communication systems. The book provides analysis of the results obtained from subjecting the developed system to environmental noise.